A Literature Review on Warehouse Location Selection - Selection Criteria and Fuzzy Methods - Sahin, Gulsah; Cebi, Selcuk (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
The selection of warehouse location is a critical strategic decision that directly affects the efficiency of logistics processes. The strategic selection of a warehouse location can facilitate business optimization, leading to enhanced cost efficiency and elevated customer satisfaction. In this study, a systematic literature review on warehouse location selection was conducted. In this context, the initial aim is to expound the criteria that are taken into consideration when selecting a warehouse location. The second objective is to express the fuzzy methods applied in the selection of warehouse location. A comparison of the fuzzy methods with classical methods is another goal of the study. In this study, a systematic literature review was conducted using the PRISMA method. For this purpose, the search was performed using the Scopus database, with the employment of relevant keywords. Afterwards, inclusion and exclusion criteria were determined according to the methodology. First, studies that were repeated were excluded from the search, followed by studies that weren't articles and whose language wasn't English. Studies that were not open source and therefore inaccessible were also excluded. The remaining studies were subjected to a comprehensive review based on title, abstract and full text, and decisions were made regarding their inclusion or exclusion. Finally, articles deemed suitable for inclusion were obtained through cross-references, and the search results were collated. The present study has the potential to contribute to the existing body of knowledge on warehouse location selection papers and to serve as a reference for future studies in this field.
Keywords: Warehouse Location Selection; Fuzzy Methods; Systematic iterature Review; PRISMA; SUPPLY CHAIN; MODEL; Computer Science; Mathematics